Immunogenicity and safety of a live-attenuated SARS-CoV-2 vaccine candidate based on multiple attenuation mechanisms - Mie Suzuki Okutani; Shinya Okamura; Tang Gis; Hitomi Sasaki; Suni Lee; Akiho Kashiwabara; Simon Goto; Mai Matsumoto; Mayuko Yamawaki; Toshiaki Miyazaki; Tatsuya Nakagawa; Masahito Ikawa; et al. (eLife)
mRNA vaccines against SARS-CoV-2 were rapidly developed and were effective during the pandemic. However, some limitations remain to be resolved, such as the short-lived induced immune response and certain adverse effects. Therefore, there is an urgent need to develop new vaccines that address these issues. While live-attenuated vaccines are a highly effective modality, they pose a risk of adverse effects, including virulence reversion. In the current study, we constructed a live-attenuated vaccine candidate, BK2102, combining naturally occurring virulence-attenuating mutations in the NSP14, NSP1, spike, and ORF7-8 coding regions. Intranasal inoculation with BK2102 induced humoral and cellular immune responses in Syrian hamsters without apparent tissue damage in the lungs, leading to protection against a SARS-CoV-2 D614G and an Omicron BA.5 strains. The neutralizing antibodies induced by BK2102 persisted for up to 364 days, which indicated that they confer long-term protection against infection. Furthermore, we confirmed the safety of BK2102 using transgenic (Tg) mice expressing human ACE2 (hACE2) that are highly susceptible to SARS-CoV-2. BK2102 did not kill the Tg mice, even when virus was administered at a dose of 106 plaque-forming units (PFUs), while 102 PFU of the D614G strain or an attenuated strain lacking the furin cleavage site of the spike was sufficient to kill mice. These results suggest that BK2102 is a promising live-vaccine candidate strain that confers long-term protection without significant virulence.